O movimento pela regulamentação da Educação Domiciliar: implicações para o direito à educação no Brasil contemporâneo - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
This dissertation started from concerns about the possible regulation of Home Education in Brazil. In recent decades (21st century), the movement for the regulation of this teaching modality, which rejects school attendance, has gained notoriety and expansion in the legislative debate, through the processing of Law Projects that sought/seek to regulate the practice. Among the Law Projects that seek to regulate ED is the PL 3.179/2012, authored by Lincoln Portela - PR/MG, which was approved in the House of Representatives and went through a cycle of debates in the Federal Senate. The issue has been debated in various social spaces, so it is understood that it is of utmost importance to investigate the foundations and arguments present in these propositions. That said, it has as research object the movement for the regulation of Home Education in Brazil and, as a guiding question: What are the foundations behind the movement for the regulation of Home Education in Brazil? In this direction, the general objective of this work focuses on analyzing the movement for the regulation of Home Education in Brazil. In order to achieve the general objective, there are specific objectives: a) Address the movement for Home Education in Brazil; b) Identify the Law Projects about the regulation of Home Education at the federal level; and c) Point out limits and possibilities of the right (to education), considering the dichotomy school x Home Education. The theoretical and methodological framework is the Dialectical and Historical Materialism, which supports the approach of the categories and conceptions of law, education and society. Empirically, it was sought to analyze the Law Projects that are in progress in the Senate and in the Chamber of Deputies with the agenda of Home Education. As methodological procedures, in addition to the search and analysis of Law Projects about the regulation of Home Education in Brazil at the federal level, we reviewed the academic production, and based on some authors who advocate the modality, such as Zamboni (2020) and Moreira (2017). The study allowed identifying, regarding the debate about the regulation of Home Education, some implications, such as: the issue of education as a public right versus the defence of the parents' right to choose (private right), as well as the presence of a conservative discourse to defend the regulation of DE in Brazil. From the research data: the Law Projects, as well as the analysis of the legislative debate and the content of Bill 3.179/2012, the research results point out that the movement for the regulation of Home Education in Brazil is anchored in the defense of the individual right having as basis the search for a restricted education guided by moral and religious values of families.
Keywords: Educação Domiciliar; Homeschooling; Direito à Educação; Projetos de Lei; Home Education; Homeschooling; Right to Education; Draft Laws; CNPQ::CIENCIAS HUMANAS::EDUCACAO